The Effect of Perceived Father Involvement on Emotional Intelligence in Adolescents - Sulistyawati, Yuni (Developmental and Clinical Psychology, 2024)
The period of adolescence is often characterised by emotional agitation, creating a vulnerability to the influence of the surrounding environment. Adolescents frequently lack the capacity to recognise, regulate and control their emotions, which can result in social difficulties. This indicates that adolescents exhibit a deficiency in emotional intelligence. To fulfil their emotional intelligence, adolescence is influenced by a variety of factors, including the role of parents. Parents, as the primary figure in the care of adolescents, have a significant role in the development of adolescent emotional intelligence. The involvement of fathers in parenting is an important factor to consider when examining the relationship between fathers and their children in the context of emotional intelligence development. This study aims to determine the effect of perceived father involvement in parenting on adolescents' emotional intelligence. The research method was correlational research, conducted on a sample of 180 adolescents in Indonesia, aged between 13 and 18 years. A convenience sampling technique was used for the selection of participants. The father's involvement scale consists of 27 items with an alpha coefficient of 0.959, while the emotional intelligence scale consists of 12 items with a coefficient of 0.868. In this study, the hypothesis test is a simple linear regression analysis, using JASP 0.18.3 software. The findings of this study evidenced a significant influence between adolescents' perceptions of father involvement and their emotional intelligence. Furthermore, this study emphasises that adolescents with divorced parents have positive perceptions of father involvement and their emotional intelligence.